Biomechanics of rotational movement in off-ice figure skating jumps: Applications to training - Mazurkiewicz, A. (Polish Journal of Sport and Tourism, 2021)
The aim of this study was to characterize kinematic parameters of the rotational body movement during the office figure skating multi-revolution jumping exercise and to propose applications to training.